ALARP demonstration in management of change using quantitative Bowtie analysis risk assessment tool for an offshore gas platform - Abdul Aziz, Mohammad Afif; Md Said, Mohamad Syazarudin (Wiley, 2023)
In this study, a framework for a quantitative Bowtie analysis based on the layer of protection analysis (LOPA) approach in the management of change (MOC) process flow was developed. The proposed tool can be used as a quantitative risk analysis method in supporting decisions when layers of protection or safeguards are unavailable. The proposed tool can quantify the frequency of the causes of a particular hazard via Fault Tree Analysis and identify the multiple consequences of the impact of the hazards with quantitative end events for risk analysis. The practicality of the proposed tool was demonstrated in a selected case study from the MOC database from Company A's offshore gas platform, where the consequences and impacts of the hazards to the people, environment, assets, and reputation were assessed. The LOPA quantification was introduced into the Bowtie diagram using a reliability database to determine the failure rates and probability of failure of the affected equipment. The risk tolerance level was subsequently determined. The outputs of risk analysis from the proposed quantitative Bowtie were then compared with the previous qualitative risk evaluation of the selected case study. Potential opportunities for further use of the proposed quantitative Bowtie tool were recommended.